Antibodies to 5 M urea soluble chromosomal proteins from HeLa cells - Dunn, B; Mendelson, E; Soares, N; Bustin, M (Biochimica et biophysica acta, 1985)
The tissue specificity of a chromosomal protein fraction, extractable from chromatin with 5 M urea at low ionic strength, has been examined in HeLa, A549 and HT 29 cells. Electrophoresis in polyacrylamide gels indicates that each cell type has a different content of 5 M urea soluble proteins which are distinguishable from the histones, from the tight DNA-binding proteins and from the high-mobility-group chromosomal proteins. Antibodies against 5 M urea soluble proteins extracted from HeLa cells were produced in mice. Although each of the mice tested prior to immunization contained a detectable amount of antibodies against both the 5 M urea soluble proteins and tight DNA-binding proteins, immunization elevated the level of the antibodies in the serum over 100-fold. The antibodies do not distinguish between the 5 M urea extracts obtained from different sources because most of the antibodies are directed against antigens shared by the cells studied. Immunofluorescence studies reveal that components which cross-react with 5 M urea soluble chromosomal proteins are also present in the cytoplasm. We conclude the following. (1) 5 M urea extracts from chromatin a group of proteins which differs among cells. (2) Mice contain detectable amounts of autoantibodies against these chromosomal proteins. (3) Immunization with the 5 M urea extractable fraction elicits antibodies against a restricted number of antigenic components which are shared among the cells studied. (4) 5 M urea extractable proteins are found both in the nucleus and cytoplasm; part of these may be cytoskeletal elements. Because the antisera do not react with histones, high-mobility-group proteins and tight DNA-binding proteins, they may be used for various functional studies on the 5 M urea extractable chromosomal protein fraction.